Planurile de separație în realismul lui Agârbiceanu - Mihăiță Stroe (Revista de Istorie și Teorie Literară)
This text is part of a larger chapter of a doctoral thesis under development, which aims to address the life and work of the writer Ion Agârbiceanu. This fragment visits the volume Introduction to the work of Ion Agârbiceanu by Mircea Popa (Minerva Publishing House, 1982), a work that seeks to demonstrate the realistic character of the Transylvanian author’s work, saving him from the tendentious labels of interwar criticism.